2017
DOI: 10.1093/protein/gzw075
|View full text |Cite
|
Sign up to set email alerts
|

Ligand characterization of CYP4B1 isoforms modified for high-level expression inEscherichia coliand HepG2 cells

Abstract: Human CYP4B1, a cytochrome P450 monooxygenase predominantly expressed in the lung, inefficiently metabolizes classical CYP4B1 substrates, such as the naturally occurring furan pro-toxin 4-ipomeanol (4-IPO). Highly active animal forms of the enzyme convert 4-IPO to reactive alkylating metabolite(s) that bind(s) to cellular macromolecules. By substitution of 13 amino acids, we restored the enzymatic activity of human CYP4B1 toward 4-IPO and this modified cDNA is potentially valuable as a suicide gene for adoptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 56 publications
(63 reference statements)
2
23
0
Order By: Relevance
“…However, acyl-CoA dehydrogenase, short/branched chain ( ACADSB ), acyl-CoA dehydrogenase family member 11 ( ACAD11 ), and cytochrome P450 ( CYP4B ) were downregulated by the Thr-D diet. These genes are involved in fatty acid β-oxidation and ω-oxidation (Vockley et al, 2000; He et al, 2011; Hsu et al, 2017; Roellecke et al, 2017; Scott, 2017). The Thr-D diet downregulated the expression of carnitine palmitoyltransferase 1B ( CPT1B ) compared with the Pair-F diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, acyl-CoA dehydrogenase, short/branched chain ( ACADSB ), acyl-CoA dehydrogenase family member 11 ( ACAD11 ), and cytochrome P450 ( CYP4B ) were downregulated by the Thr-D diet. These genes are involved in fatty acid β-oxidation and ω-oxidation (Vockley et al, 2000; He et al, 2011; Hsu et al, 2017; Roellecke et al, 2017; Scott, 2017). The Thr-D diet downregulated the expression of carnitine palmitoyltransferase 1B ( CPT1B ) compared with the Pair-F diet.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 2-HepF and 2-AF resulted in nonspecific toxicities in the cells. 68 These findings suggested significant variations with regard to the substrate specificities among the CYP4B1 enzymes, which has been summarized in Table 3.…”
Section: Cyp4b1 In Carcinogenesismentioning
confidence: 94%
“…67 Furthermore, perilla ketone (PK), isolated from the oil of Perilla frutescens, shares similar chemical structure with 4-IPO, which is also a well-known pneumotoxin. 68 Thus, Roellecke et al developed PK as an alternative prodrug of 4-IPO to be used in this suicide gene system. 67 The following studies carried out by Roellecke group aimed to identify more new alternative prodrugs to be applied in the suicide gene system (HepG2 cells) expressing four different CYP4B1 enzymes, including the rabbit wild type (r-P422), the human wild type (h-S427), the human activated (h-P427), and human reengineered (CYP4B1Pþ12) proteins.…”
Section: Cyp4b1 In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Use of OB ≥30% and DL ≥0.18 as the screening criteria yielded 14 active components. An analysis of the published literature revealed that although (s)carvone (Alasanea and , caffeic acid (Tyszka-Czochara et al, 2018), rosmarinic acid (Colica et al, 2018), caryophellene (Sharma et al, 2016), perilla aldehyde (Song et al, 2018), and perilla ketone (Roellecke et al, 2017) did not meet the aforementioned OB and DL screening criteria, in vivo and in vitro experiments were validated. Therefore, these components were included to result in 19 main active components (C20 Supraene did not retrieve the predicted target, and so was excluded in further research) (Table 1 and Supplementary Figure S1).…”
Section: Main Active Components and Targets Of P Frutescensmentioning
confidence: 99%